Africa: Information Technology in African Business (it@ab) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Information Technology in African Business (it@ab) aims to enhance business development and business information management through coordinated IT training programmes in the SADC region.